Runs on money market mutual funds - Lawrence Schmidt; Allan Timmermann; Russ Wermers (University of Cologne, Centre for Financial Research (CFR), 2014)
We study daily money market mutual fund flows at the individual share class level during the crisis of September 2008. The empirical approach that we apply to this fine granularity of data brings new insights into the investor and portfolio holding characteristics that are conducive to run-risk in cash-like asset pools, as well as providing evidence on the time-series dynamics of runs and the equilibria that develop. We propose two identification approaches to test predictions of recent theoretical models with strategic complementarities and incomplete information. First, we study dynamic interactions between investors with differing levels of sophistication within the same money fund, thus holding constant the quality of the underlying portfolio. Second, we employ a novel quantile regression methodology to identify relationships between observable characteristics and tail outcomes. Our results provide considerable support for the theoretical predictions, providing some of the strongest empirical evidence to date on run-like behavior within intermediated asset pools during the financial crisis.
Keywords: G01; G21; G23; 330; money market mutual funds; bank runs; strategic complementarities; quantile regression